Faktor yang Mempengaruhi Siklus Menstruasi pada Mahasiswi di Depok, Indonesia: Factors Influencing the Menstrual Cycle of Female College Students in Depok, Indonesia - Fitri, Syania; Sofianita, Nur Intania; Octaria, Yessi Crosita (Amerta Nutrition, 2024)
Background: Adolescence is a critical period in life when reproductive organs mature and develop, especially in teenage girls. The menstrual cycle plays a crucial role in female reproductive health, often disrupted by various factors. Objectives: This research aims to identify factors affecting the menstrual cycle in female college students in Depok. Methods: This cross-sectional study involved 193 participants selected through stratified random sampling. Data collection included fast food consumption habits (measuring frequency and the amount of fat intake) using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), sleep quality assessment using the Pittsburgh Sleep Quality Index (PSQI), stress levels evaluation using the Perceived Stress Scale-10 (PSS-10), and menstrual cycles assessment using the menstrual cycle questionnaire. Statistical analysis employed chi-square tests and multiple logistic regression. Results: No significant correlation was observed between the frequency of fast food consumption and the menstrual cycle (p-value=0.780). Conversely, fat intake (p-value=0.027; OR=2.6), sleep quality (p-value=0.009; OR=10.8), and stress levels (p-value<0,001; OR=7.19) showed a significant correlation with the menstrual cycle. Multivariate analysis identified stress level as the predominant factor (p-value<0.001; OR=9.411). Conclusions: This research concluded that there is a significant correlation between fat intake, sleep quality, stress levels, and the menstrual cycles among college students in Depok. Stress level emerged as the primary factor affecting adolescent respondents' menstrual cycles.